Implications of carrier identification in newborn screening for cystic fibrosis. Issue 6 (1st November 2003) - Parsons, E P; Clarke, A J; Bradley, D M
Abstract : Objective: To investigate the psychosocial implications for families whose infant was identified as a cystic fibrosis carrier by newborn screening. Design: Prospective psychosocial assessment. Setting: Primary care. Respondents: Study: ( a ) families of an affected infant identified by screening (n = 9); ( b ) families of a carrier infant identified by screening (n = 10). Control: group of mothers from the general population (n = 82). Interventions: Questionnaires and semistructured interviews. Main outcome measures: Attitude to screening, assessments of the mother/baby relationship, anxiety, wellbeing. Results: All families were in favour of screening, with no evidence that the mother/baby relationship, anxiety or wellbeing had been adversely affected. Parents, however, did identify problems in terms of the service delivery protocol and genetic counselling practice. Conclusion: Six months after disclosure, carrier identification was not perceived by parents to be problematic.